Impact assessment of the social housing program of the city of Las Piñas - Ignacio, Eunice Anne C.; Padero, Ann Karla D.; Soriano, Rosette G. ([National College of Public Administration and Governance, University of the Philippines Diliman], 2012)
Shelter and housing problems are prevalent in urban location around the globe, especially in developing countries. In the Philippines, where most of the population converges in the cities for employment opportunities and better living conditions, shelter problems get increasingly unmanageable. This paper briefly discusses the impact of urban migration and how it relates to informal settling, and the development of urban land tenure in the country as regards to housing. After reviewing the main ideas of shelter and housing in the public setting, e.g. shelter being provided as a public good, this paper assesses the current situation in the City of Las Piñas with respect to the current program the local government unit is implementing, entitled "Integrated Shelter & Land Tenure for the Urban Poor to Effectively Reduce the Incidence of Poverty and Homelessness in Las Piñas City". This project deals with individual structures for housing single households and providing them with land tenure. This paper evaluated the project in terms of its impact, which includes social and economic factors, to ascertain whether the objectives of the project for its beneficiaries were met. The study also compared the data gathered from beneficiaries and non-beneficiaries to determine the impact of the project.